Actin microheterogeneity in chick embryo fibroblasts. - Rubenstein, P A (1977)
Secondary chick embryo fibroblasts contain three distinct actin species--alpha, beta, and lambda, in the approximate ratio of 1:6:3--with the same molecular weights but different isoelectric points. The most acidic of these components, alpha, comigrates on isoelectric focusing gels with the major actin of cardiac and skeletal muscle, while lambda, the most basic of the actins, comigrates with smooth muscle actin. The three components have overlapping methionine-containing tryptic peptides. All three actins are found to be present in actomyosin and cytoskeleton preparations from chick embryo fibroblasts. Identification of alpha-actin as the major actin from sarcomere-containing cells is confirmed by comparing embryonic chicken pre- and post-fusion myoblast cultures. Following myoblast fusion, the relative amount of alpha-actin increases until it changes from a minor actin component to the predominant actin species in the culture.